Sexual Bias and Household Consumption: A Semiparametric Analysis of Engel Curves in Rural China - Xiaodong Gong; Arthur van Soest; Ping Zhang (Institute for the Study of Labor (IZA), 2000)
We analyze Engel curves for nuclear households in rural China. The sample includes more than 5000 nuclear families covering nineteen out of thirty Chinese provinces. We consider expenditures on food, also subdivided into several food subcategories such as cereals, or meat and fish, and other consumption categories such as alcohol and tobacco, medical, and educational goods. We use the semiparametric partially linear model. This allows for any functional form relationship between the budget shares and total expenditures, but assumes that the demographic variables enter the model in a linear way. We correct for potential endogeneity of total expenditures. Our results suggest that there are economies of scale in families ?consumption expenditure patterns. We find some differences in consumption patterns which relate to differences in gender of children, which can be seen as evidence of sexual bias related to a commonly believed existing preference for boys.
Keywords: C14; D63; J16; C20; R20; D12; 330; Household economics; consumption; bias; gender differences; Engel curve; China; Mikroökonomische Konsumfunktion; Geschlecht; Schätzung; China